Analisis Berpikir Kritis Siswa MTs Negeri 1 Sampang pada Pembelajaran IPA dengan Menggunakan Model Problem Based Learning - Raudatul Jannah (AIJER: Algazali International Journal Of Educational Research, 2022)
Abstract: Critical Thinking Analysis of MTs Negeri 1 Sampang Students in Science Learning using a Problem Based Learning Model. The purpose of this study is to describe problem-solving abilities in science learning using the Problem Based Learning (PBL) model and to improve understanding of science learning by improving student learning outcomes. This class action research is motivated by the low scores of students in science subjects. This type of research uses qualitative descriptive research. Observation, interviews and documentation are used as data collection techniques. Data are analyzed through data reduction, presentation and inference. The subjects of this study were students of MTs Negeri 1 Sampang class VIII B. Research results showed that the PBL model can improve problem solving, can improve student performance in learning activities, material that is considered difficult, can improve student concepts, concretize to students through a learning environment. To provide information and improve student learning. In summary, the PBL model can improve student learning outcomes in science learning class VIII B at MTs Negeri 1 Sampang.